Identifying potential functional impact of mutations and polymorphisms: linking heart failure, increased risk of arrhythmias and sudden cardiac death - JAGU, BENOIT; CHARPENTIER, FLAVIEN; TOUMANIANTZ, GILLES (Frontiers in Physiology, 2013)
Researchers and clinicians have discovered several important concepts regarding the mechanisms responsible for increased risk of arrhythmias, heart failure and sudden cardiac death. One major step in defining the molecular basis of normal and abnormal cardiac electrical behaviour has been the identification of single mutations that greatly increase the risk for arrhythmias and sudden cardiac death by changing channel-gating characteristics. Indeed, mutations in several genes encoding ion channels, such as SCN5A, which encodes the major cardiac Na+ channel, have emerged as the basis for a variety of inherited cardiac arrhythmias such as long QT syndrome, Brugada syndrome, progressive cardiac conduction disorder, sinus node dysfunction or sudden infant death syndrome. In addition, genes encoding ion channel accessory proteins, like anchoring or chaperone proteins, which modify the expression, the regulation of endocytosis and the degradation of ion channel α-subunits have also been reported as susceptibility genes for arrhythmic syndromes. The regulation of ion channel protein expression also depends on a fine-tuned balance among different other mechanisms, such as gene transcription, RNA processing, post-transcriptional control of gene expression by miRNA, protein synthesis, assembly and post-translational modification and trafficking.